Gastrointestinal perforations in newborns with high mortality: A series of 18 cases - Monsoia Gildas Yassegoungbe; Beaudelaire Romulus Assan; Amoussou Sedjro Clotaire Romeo Houegban; Djifid Morel Seto; Codjo Serge Metchihoungbe; Eudes Ulrich Elvis Mahougnon Goudjo; Houenoukpo Koco; Sourou Bruno Noukpozounkou; Aldrico Pautin Covi; Michel Armand Fiogbe (EL-Med-Pub, 2020)
Gastrointestinal perforations (GIP) in newborns are serious neonatal conditions that have significant morbidity and mortality, especially in resource constrained setups. This study was done to describe our experience of GIP in neonates and identify the factors leading to high mortality in our setup. We collected 18 cases with GIP in neonates. The average age was 5.7 days (range, 1-7 days). The sex ratio was 0.64. The average time to treatment was 3.3 days (range, 1-10 days). The etiology of GIP was perforated necrotizing enterocolitis (13 patients), spontaneous gastric perforation (2 patients), perforated ileal atresia (1 patient), ileal perforation complicating a strangulated inguinoscrotal hernia (1 patient), and peritonitis after colostomy (1 patient). Mortality was 77.8% (n=14), among which 9 newborns (64.3%) died preoperatively. Prematurity, management delay, and lack of a neonatal intensive care unit were the main poor prognostic factors. Mortality from GIP is still high in our context due to several factors, especially prematurity, management delay, and lack of a neonatal intensive care unit.